PENGARUH PENERAPAN GREEN ACCOUNTING DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS PERUSAHAAN DENGAN CITRA PERUSAHAAN SEBAGAI VARIABEL MODERATING - Mohamad Soedarman Soedarman; Abigail Fenina; Lailatus Sa’adah (Prodi Akuntansi FEB UNITOMO, 2023)
This study aims to analyze the influence between green accounting and Corporate Social Responsibility variables on company profitability and the effect between green accounting and Corporate Social Responsibility which is moderated by corporate image on company profitability. The results of this study are expected to be able to contribute to company management in applying these two concepts as an effort to maximize profitability and corporate image. This research method uses a quantitative causality approach. The sampling technique used purposive sampling and obtained a sample of 16 food and beverage companies. Data processing uses SmartPLS 4. The results of this study show that green accounting has a negative and not significant effect on profitability, Corporate Social Responsibility has a negative and significant effect on company profitability, green accounting has a negative and significant effect on company profitability through corporate image, and Corporate Social Responsibility has a positive effect and not significant to company profitability through corporate image.